Das „antipandektistische Manifest“ von Leonard Piętak - Ernest Bodura (PÁZMÁNY LAW REVIEW, 2021)
This essay deals with the programmatic advance of one of the leading representatives of the non-pandectist current in Roman law studies in Galicia in the second half of the XIX century, the Lviv Professor of Roman Law Leonard Piętak (1841–1909). In a manual of Roman inheritance law published in 1882 Piętak wrote a kind of methodological credo of the anti-pandectist current within Galician Roman law studies. In the introduction to the aforementioned handbook he announced that he intended to deal exclusively with pure Roman law. In this context, he emphatically stated: The pandect law of the 19th century was, strictly speaking, to a large extent no longer Roman law at all and was, therefore, completely dispensable in the contemporary teaching of Roman law. In the opinion of the author of the present essay, Piętak‘s initiative at that time may be described as an „anti-pandectist manifesto“ of Galician Roman law studies from today‘s legal historical perspective.